On the mechanism of the cholesterol lowering ability of soluble dietary fibers: Interaction of some bile salts with pectin, alginate, and chitosan studied by isothermal titration calorimetry - Massa, Michele; Compari, Carlotta; Fisicaro, Emilia (Frontiers in Nutrition, 2022)
Reducing high blood cholesterol is an important strategy to decrease the chances of a cardiovascular disease occurrence, the main cause of mortality in western developed countries. Therefore, the search for an alternative therapeutic or preventive approach being natural, biocompatible, and not toxic is still more relevant than ever. This need is particularly felt in Pediatrics for treating childhood hypercholesterolaemia, due to statins interference in the production of steroid hormones in prepuberal children. Notwithstanding the general acceptance of the healthy role of the fibers in the diet, the mechanism underlying the cholesterol-lowering ability of soluble fibers is still under discussion. Therefore, we started a systematic study of the binding ability of some soluble dietary fibers (SDF) originated from different natural sources towards selected bile salts (BS) by isothermal titration calorimetry (ITC). Here we report the results of our ITC studies on the interaction of alginate, pectin and chitosan with sodium cholate (NaC), sodium deoxycholate (NaDC), sodium taurocholate (NaTC) and sodium taurodeoxycholate (NaTDC). Thermodynamic data on the micelle formation process of the above bile salts, as a premise to the study of their binding ability to the SDF, are also reported. Alginate does not show specific binding interaction with BS, while pectin shows a strong exothermic bond with NaDC in monomeric form. Chitosan, positively charged and soluble only at low pH, shows strong exothermic interactions with NaTC and NaTDC (soluble at pH=3 in acetate buffer) with precipitate formation. For NaTC, the exothermic peak starts at about 5 mM. At this concentration NaTC bound on the fiber reaches locally the cmc value and micelles start forming on the fiber inducing its conformational change. For NaTDC the same process occurs at much lower concentrations, due to lower cmc, and with a greater quantity of heat involved. The first set of results here presented shows that for some SDF the binding of BS could be an important mechanism in cholesterol lowering but not the only one. The information here presented could be a starting point for the design of optimized functional foods with high cholesterol lowering ability.